PERLINDUNGAN HUKUM TERHADAP INVESTOR YANG GAGAL MELAKUKAN DUE DILIGENCE SEHINGGA TERJEBAK INVESTASI BODONG - Suryani, Ummi; Sirait, Ningrum N.; Robert, Robert (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: Due diligence prior to investing, whether conducted independenly by investors or with the assistance of legal consultants, is a form of precautionary action to avoid fraudulent/illegal invesments. The Financial Services Authority’s efforts in preventing fraudulent/illegal invesment through socialization and education to the public are essential for ensuring legal protection for investors. The methodology employed in this thesis is a normative juridical research method, which refers to legal norms and is conducted through library research. This study is descriptive in nature, and the data analysis method used is qualitative. The research findings reveal that the legal aspect of due diligence by investors in invesment activities involves the participation of legal consultants, with the investor acting as the implementer of the due diligence process. This is done to assess and consider invesment opportunies, thus preventing involvement in fraudulent invesments. The Financial Services Authority’s actions in regulating and supervising investors to perform due diligence in order to prevent fraudulent invesments are in accordance with Law  Number 4 of 2023 on the Development and Strengthening of the Fnancial Sector, amending Law Number 21 of 2011 on the Financial Services Authory. Legal protection for investors who fail to conduct due diligence and fall victim to fraudulent invesments can be viewed from the perspective of personal responsibility and the responsibility of the legal consultants if their services were utilized. Keyword: Invesment, Due Diligence, Legal Protection Abstrak: Due diligence dapat dilakukan oleh investor secara mandiri dan menggunakan jasa konsultan hukum adalah sebagai bentuk tindakan investor agar terhindar dari investasi bodong/illegal. Tindakan Otoritas Jasa Keuangan dalam pencegahan investasi bodong/illegal dengan cara sosialisasi dan edukasi kepada masyarakat, sehingga perlindungan hukum terhadap investor dapat dilaksanakan. Metode yang digunakan dalam penulisan tesis ini adalah metode penelitian yuridis normative, yaitu metode yang mengacu pada norma hukum yang dilakukan dengan studi Pustaka. Penelitian ini memiliki sifat deskriptif. Metode Analisa data yang digunakan adalah kualitatif. Hasil penelitian menemukan bahwa aspek hukum pelaksanaan due diligence oleh investor dalam kegiatan investasi adalah dengan melibatkan konsultan hukum dan investor sebagai pelaksana dari proses due diligence tersebut. Hal ini dilakukan untuk pemeriksaan dan pertimbangan investor agar terhindar dari investasi bodong. Tindakan Otoritas Jasa Keuangan dalam menerapkan pegaturan dan pengawasan investor dalam melaksanakan due diligence untuk mencegah investasi bodong adalah sesuai dengan Undang-Undang Nomor 4 Tahun 2023 Tentang Pengembangan dan Penguatan Sektor Keuangan atas Perubahan Undang-Undang Nomor 21 Tahun 2011 Tentang Otoritas Jasa Keuagan. Perlindungan hukum terhadap investor yang gagal melakukan due diligence sehingga terjebak investasi bodong dapat dilihat dari segi tanggungjawab mandiri dan tanggungjawab konsultan hukum apabila menggunakan jasa konsultan hukum. Kata kunci: Investasi, Due Diligence, Perlindungan Hukum